Common variation in KITLG and at 5q31.3 proximate to SPRY4 predispose to testicular germ cell cancer - Kanetsky, Peter A. (2009)
Evidence suggests that testicular germ cell tumors (TGCT) have a strong underlying genetic component. We performed a genome-wide scan among 277 TGCT cases and 919 controls. Seven markers at 12p22 within c-KIT ligand (KITLG) reached genome-wide significance (P < 5.0 × 10(−8)). In independent replication, TGCT risk was increased 3-fold per copy of the major allele at rs3782179 and rs4474514 (OR=3.08, 95% CI 2.29, 4.13; OR=3.07, 95% CI 2.29, 4.13, respectively). We also replicated associations with rs4324715 and rs6897876 at 5q31.3 near sprouty 4 (SPRY4; P < 5.0 × 10(−6) in discovery). Risk of TGCT was increased nearly 40% per copy of the major allele (OR=1.37, 95% CI 1.14, 1.64; OR=1.39, 95% CI 1.16, 1.66, respectively). All of the genotypes were associated with both seminoma and non-seminoma TGCT subtypes. These results demonstrate that common genetic variants affect TGCT risk and implicate KITLG and SPRY4 as TGCT susceptibility genes.